Fish welfare (Blackwell Pub, 2008)
With the rise of the aquaculture industry during recent years and its likely continuing expansion for very many years, the subject of fish welfare has come to the fore, although the subject is in its infancy. This important new book represents a landmark in the subject area, bringing together a great wealth of relevant information together in the covers of one book for the first time. Fish Welfare is broadly divided into two sections. The first section deals with general aspects of fish welfare including chapters covering how fish suffer pain and fear, fishesrsquo; responses to stress and the measurement of such stress responses, and a summary of the current legislation relevant to fish welfare. The second section of the book covers welfare issues relating specifically to aquaculture and includes major topics such as stocking densities, water quality, physical trauma, diseases, feeding, pre-slaughter handling and slaughter, and fish transport. Carefully edited by well-known fish veterinarian Edward Branson, Fish Welfare brings together contributions from many of the most highly respected scientists currently working in the area. Fish Welfare is an essential purchase for fish farm managers, all fish veterinarians and those involved in the aquaculture industry and its regulation.